Desain dan Pengembangan Website Pada Yayasan Baitul Husna Harapan Indah - Jayanti, Nila Rusiardi; Sandy, Agung Ferdinan; Anshary, Nico Bustanul (LP2M STAI Darul Kamal NW Kembang Kerang-NTB, 2025)
In this digital era, the existence of website is important for organizations, legal entities, one of which is Yayasan. The website functions as a platform contains various multimedia documents and can be accessed in branding, promotion and consumer services, it is very necessary as a profile can be trusted by public. In terms of community service activities, we partner with Baitul Husna Harapan Indah Bekasi Yayasan, which is engaged social, religious, humanitarian and educational fields. Yayasan wants to increase the dissemination of information related to their vision, mission and work programs through digital platform, namely website. Currently, our partner already has Yayasan website, namely https://www.masjidbaitulhusna.com . Our partner conveyed problems faced, namely reduced user access, due to limited features and a less eye-catching website appearance, which is obstacle to access by website users. Therefore, PKM Team tried to provide solution, namely creating UI/UX layout design and website development with additional features and will also educate Yayasan's administrators to be able to operate website and carry out further development. It is hoped that results of the PKM Team's community service activities can provide real benefits in improving quality of services from Baitul Husna Harapan Indah Bekasi Yayasan to wider community.